EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS PROYEK BERBANTUAN PHET SIMULATION DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS XI PADA MATERI ASAM BASA - Erik Farjemi; Eka Junaidi; Yunita Arian Sani Anwar (FKIP University of Mataram, 2026)
Low student motivation and learning outcomes are often attributed to the continued use of conventional teaching methods and the limited integration of interactive learning media. This study aimed to determine the effectiveness of the Project-Based Learning (PjBL) model, assisted by the PhET Simulation, in improving the motivation and learning outcomes of eleventh-grade students on the acid–base topic. The research was conducted at SMAN 2 Praya using a quantitative approach with a pretest–posttest control group design. The samples were randomly selected, with class XI F1.1 serving as the experimental group, which received Project-Based Learning (PjBL) assisted by PhET Simulation, and class XI F1.2 serving as the control group, which received conventional instruction. Data were collected via a learning motivation questionnaire and psychomotor learning outcome assessments, and analyzed using MANOVA. The results showed that the average learning motivation score in the experimental class increased from 67.93 to 72.52, while learning outcomes improved from 33.34 to 84.37. In the control class, learning motivation changed from 63.80 to 73.93, and learning outcomes increased from 28.26 to 79.67. The MANOVA test yielded a p-value of 0.000 (p < 0.05), indicating a significant simultaneous difference between the experimental and control groups in students’ motivation and learning outcomes. Therefore, the Project-Based Learning (PjBL) model assisted by PhET Simulation was found to be effective in enhancing students’ motivation and learning outcomes in acid–base learning.